KONSTRUKSI BUDAYA ADIL GENDER MELALUI PERMAINAN TRADISIONAL ACEH DAN SULAWESI SELATAN PADA ANAK USIA DINI - Sarah Zulkarnaini; Musylia Nurfadlia; Marzuki Mansur (PSGA LP2M IAIN Pontianak, 2021)
This literature study aims to discuss the culture of gender equity in early childhood that is constructed through traditional games. In this study the author raised the traditional game of Aceh and South Sulawesi. Aceh is a province in Indonesia that is given the special status as a Special Region of Aceh, and South Sulawesi is a province of Indonesia in the southern part of Sulawesi with Makassar as its capital. Aceh and South Sulawesi are regions that are very rich with their local cultures, as usually in other parts of Indonesia. One aspect of regional culture develops through traditional games. At the same time, technological advances have eroded traditional games and led people (particularly children) to modern games, so that the traditional games have gradually faded. Lately, many games have been founded to have had a negative impact on early childhood, both in terms of technology and gender injustice. This provokes awareness of the need to re-popularize traditional games to help replant the special characteristics of local cultures, minimize the negative impact of technology-based games, and to dismiss games that are not gender-just. The main results of this paper are to highlight the importance of gender equity in early childhood in the permanent aspect, because games are early childhood learning activities.